Electron shuttles enhanced the removal of antibiotics and antibiotic resistance genes in anaerobic systems: A review - Deng, Yuepeng; Zhang, Kaoming; Zou, Jie; Li, Xiuying; Wang, Zhu; Hu, Chun (Frontiers in Microbiology, 2022)
The environmental and epidemiological problems caused by antibiotics and antibiotic resistance genes have attracted a lot of attention. The use of electron shuttles based on enhanced extracellular electron transfer for anaerobic biological treatment to remove widespread antibiotics and antibiotic resistance genes efficiently from wastewater or organic solid waste is a promising technology. This paper reviewed the development of electron shuttles, described the mechanism of action of different electron shuttles and the application of enhanced anaerobic biotreatment with electron shuttles for the removal of antibiotics and related genes. Finally, we discussed the current issues and possible future directions of electron shuttle technology.